Web and Android-Based Motorcycle Service and Maintenance Application - Eldyan Wasis Aristo Kana; Adam Sekti Aji (Lembaga Komunitas Informasi Teknologi Aceh (KITA), 2024)
The study is to develop a web- and Android-based application for motorcycle servicing and maintenance in helping Bendho Motor in sales tracking records as well as reporting. Application helps mechanics drive business and the owner to have effective sales performance checks. First data collection were watched workshop work and the understanding of practice business processes, interviews to workshop owner to know his/her operational difficulties. We did system analysis so as to apply the application in PHP, CSS and further frameworks. Service orders were previously manually registered leading to problems including incorrect data, illegible and lost receipts. The proposed app solves the problems of storing order histories securely and guarantee integrity of transaction.